New data on the genus Uroseius Berlese (Acari: Mesostigmata: Uropodina: Trachytidae) with a redescription of U. sorrentinus (Lombardini, 1952) - Moraza, María L. (Zootaxa, 2019)
Uroseius sorrentinus is redescribed based on nymphal instars and adults of both sexes from a cave in Southern Spain. New observations of the ontogeny of setae, glands and lyrifissures on the idiosoma and legs are provided, allowing for the clarification and expansion of the diagnostic characters of the genus UroseiusThe female of this species is distinguished from other Uroseius species by its: rounded idiosoma, with prominent anteriorly knobbed vertex; medial dorsal shield with approximately 26 pairs of short, brush-like setae; pigmented soft cuticle at posterior margin of dorsal shield with one pair of long setae; genital shield with spine-like anterior process with anterior half covered by soft sternal cuticle; and 15–20 pairs of feathered ventral setae of heterogeneous length. Males are distinguished by their: femora, genu and tibia with seta av modified as spurs; and tarsus II with two enlarged, spine-like setae. Deutonymphs are distinguished by their: dorsal shield not covering vertical and dorsolateral regions; presternal transverse sclerite present; sternal shield entire; sternal region with three pairs of conspicuous gland openings; and ventrianal shield with 8–10 pairs of setae. A key to the species of deutonymphs of Uroseius is given..